HINDU-BUDDHIS DALAM BINGKAI BUDAYA JAWA ASLI - Tjahjono, Baskoro Daru (BRIN, 1995)
Hinduism and Buddhism originated in India, entered Indonesia almost at the same time, namely around the first century AD. This culture that originated from India is often referred to as Hindu culture only. This cultural influence has not only led the Indonesian nation to enter the historical era but has also brought about major changes in various aspects of life, such as religion, government structures, and other aspects of society.